2012
DOI: 10.3349/ymj.2012.53.6.1085
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Induces Neurotrophin-3 in Rat Submandibular Gland

Abstract: PurposePlasma neurotrophin-3 (NT-3) levels are associated with several neural disorders. We previously reported that neurotrophins were released from salivary glands following acute immobilization stress. While the salivary glands were the source of plasma neurotrophins in that situation, the association between the expression of neurotrophins and the salivary gland under chronic stress conditions is not well understood. In the present study, we investigated whether NT-3 levels in the salivary gland and plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In the present study, group II had high levels of NT-3 mRNA gene expression within the submandibular gland. This is in accordance with Saruta et al [51] , who observed that immobilization stress increases NT-3 mRNA levels n the rat hippocampus. This finding may be due to the presence of high brain NT-3 level which are markedly affected by stressful events.…”
Section: Discussion:-supporting
confidence: 93%
“…In the present study, group II had high levels of NT-3 mRNA gene expression within the submandibular gland. This is in accordance with Saruta et al [51] , who observed that immobilization stress increases NT-3 mRNA levels n the rat hippocampus. This finding may be due to the presence of high brain NT-3 level which are markedly affected by stressful events.…”
Section: Discussion:-supporting
confidence: 93%
“…We previously reported that the salivary glands regulate the levels of certain substances in the blood and therefore can exert systemic effects via the bloodstream. 14,25,26) LF is produced by the salivary glands and is more abundant in the saliva than in the blood. 27) LF is useful for targeted delivery into the brain 10) because the transferrin receptor is overexpressed in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Because mice show nocturnal behavior, they were restrained from 1800 to 1000 h (16 h) for 3 consecutive days. After release from the restraining mesh, they were returned to their cages and given access to food and water, as were the controls 27,28…”
Section: Methodsmentioning
confidence: 99%
“…After release from the restraining mesh, they were returned to their cages and given access to food and water, as were the controls. 27 , 28 …”
Section: Methodsmentioning
confidence: 99%